2020
DOI: 10.1111/dom.13955
|View full text |Cite
|
Sign up to set email alerts
|

Semaglutide (SUSTAIN and PIONEER) reduces cardiovascular events in type 2 diabetes across varying cardiovascular risk

Abstract: Aim To investigate the effects of semaglutide versus comparators on major adverse cardiovascular events (MACE: cardiovascular [CV] death, nonfatal myocardial infarction [MI] and nonfatal stroke) and hospitalization for heart failure (HF) in the SUSTAIN (subcutaneous semaglutide) and PIONEER (oral semaglutide) trials across subgroups of varying CV risk. Methods Post hoc analyses of individual patient‐level data combined from SUSTAIN 6 and PIONEER 6 were performed to assess MACE and HF. MACE were analysed in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 43 publications
(127 reference statements)
4
118
0
2
Order By: Relevance
“…Our results are consistent overall with a post hoc analysis of pooled SUSTAIN and PIONEER data, which also showed that the effect of semaglutide vs comparators on MACE was largely consistent across different CV subgroups [35]. Furthermore, a meta-analysis including CVOTs for all GLP-1 receptor agonists found no significant heterogeneity in the effect of these therapies in subgroups with a history of CVD vs those with no history of CVD [36].…”
Section: Findings In Context Of the Broader Literaturesupporting
confidence: 89%
“…Our results are consistent overall with a post hoc analysis of pooled SUSTAIN and PIONEER data, which also showed that the effect of semaglutide vs comparators on MACE was largely consistent across different CV subgroups [35]. Furthermore, a meta-analysis including CVOTs for all GLP-1 receptor agonists found no significant heterogeneity in the effect of these therapies in subgroups with a history of CVD vs those with no history of CVD [36].…”
Section: Findings In Context Of the Broader Literaturesupporting
confidence: 89%
“…The HR for the expanded MACE outcome (consisting of the primary outcome plus unstable angina resulting in hospitalization or heart failure resulting in hospitalization) was similar to that of the primary outcome (HR: 0.82 [95% CI: 0.61, 1.10]) [25]. PIONEER 6 demonstrated that oral semaglutide did not result in an increase in CV risk compared with placebo [25], a finding that is supported by a post-hoc analysis of CV events across the PIONEER glycemic efficacy trials [39]. The trial was an event-driven trial designed and powered to assess noninferiority of oral semaglutide to placebo, and continued until at least 122 MACE occurred, with no predefined minimum duration.…”
Section: Cardiovascular Safetymentioning
confidence: 59%
“…The trial was an event-driven trial designed and powered to assess noninferiority of oral semaglutide to placebo, and continued until at least 122 MACE occurred, with no predefined minimum duration. This design differs to that of other GLP-1RA CVOTs [30], such as SUSTAIN-6 with subcutaneous semaglutide, LEADER with liraglutide, and REWIND with dulaglutide, which reported significant reductions in risk of MACE with these agents versus placebo [18][19][20] (for an in-depth overview of the designs and outcomes of PIONEER 6 and SUSTAIN-6, see Husain et al, 2020 [39]). Like PIONEER 6, SUSTAIN-6 and LEADER were conducted primarily to establish noninferiority; however, these trials were both time-and event-driven and conducted for longer than PIONEER 6, accruing more MACE than originally planned (for example, MACE occurred in 254 patients in SUSTAIN-6, versus 137 in PIONEER 6), and therefore had greater power to evaluate the potential superiority of the study drug to placebo [18,19].…”
Section: Cardiovascular Safetymentioning
confidence: 99%
“…However, guidelines for glucose-lowering therapy take into account only general considerations of patient phenotype and comorbidities ( Table 2) rather than actual pathophysiologic mechanisms. [45][46][47][48][49][50][51][52] After studies of monozygotic twins and other evidence indicated that type 2 diabetes was a genetic disorder, there was hope that genetic information might be directly associated with specifi c pathophysiologic mechanisms Diabetes mellitus is a syndrome HOOGWERF involved in the development of hyperglycemia. These relationships might use genetic profi les to guide pharmacotherapy.…”
Section: ■ Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Some glucagon-like peptide 1 receptor agonists (liraglutide,48 dulaglutide,49 and semaglutide,50 but not lixisenatide51 or exenatide [weekly formulation])52 reduce risk of major adverse cardiovascular events…”
mentioning
confidence: 99%